TROUBLESHOOTING TEMPERATURE GAUGE ON CONTROL PANEL OF ENGINE 3066 AT ALAT BERAT WORKSHOP OF POLITEKNIK NEGERI JAKARTA - Abdul Azis Abdillah; Erifmi Zahada; Lentang B. Sibarani; Imam Wahyudi; Azwardi Azwardi; Fuad Zainuri; Haidir Juna; Memed Sumatono (Jurnal Poli-Teknologi, 2021)
Troubleshooting on the temperature gauge on the engine control panel 3066 with the serial number is 7JKa method used to find the cause of the problem with the temperature gauge. The temperature gaugecontained in the 3066 control panel engine does not work while running. Therefore, this research aims todetermine the cause of the temperature gauge on the 3066 control panel engine not functioning. The formof this research is to take data on the method of problem solving and repair of temperature gauges that areexperiencing problems by buying new components that do not use transformer step-ups. Instrumentationdata in literature research, data, visual inspection and making changes to temperature gauges. The resultsof conducting literature studies, studying data, visual inspection, and replacing the temperature gauge witha new one on the 3066 control panel engine, get the root of the problem of damage to the coil of the stepup transformer because the input voltage is too large. Keywords : Troubleshooting, Control Panel, Heavy Equipment, Temperature Gauge